Nilai Organologi Akustik Polopalo - Rahmawati Ohi (Institut Seni Indonesia Yogyakarta, 2019)
Values are meanings, messages either implicitly-exemplified in the form of ideas or theories that work in community activities, one of the material objects that describe the phenomenon is a traditional musical instrument. Speaking of traditional musical instruments, there is one that is valuable, namely Polopalo. Polopalo is a percussion instrument, a Gorontalo icon with a unique organology that is similar to a crocodile's mouth and produces a distinctive acoustic sound character. The unique and interesting aspect of Polopalo's acoustic organology makes its value function continue to experience development and transformation in the activities of society and the world of science.Nattiez about the meaning process at three levels: decomposition of acoustic components, historical or cultural background and physio-acoustic response and supported by the Alperson-Bordieu theory so that the research method uses quantitative-qualitative.The results showed that the value of Polopalo's acoustic organology is the embodiment of the character and philosophy of the Gorontalo people in everyday life where the existence of the sign is represented by the unique sound frequency and interval